Transformation and global expansion of the Brazilian aviation industry at the turn of the 21st century on the example of Embraer - Wójtowicz, Mirosław (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2010)
The aim of the study is to analyse the process of historical growth, transformation and global expansion of the largest Brazilian aircraft industry enterprise - Embraer (Empresa Brasileira de Aeronautica). The company history can be divided into three main stages. The first one lasted from 1969 until the second half of the 1980s. In that stage, the company developed production supported mainly by the government or on license technology. The second stage lasted from the end of the 1980s to the mid-1990s. This was the stage of the crisis and transformation of the company, which ended up with its privatization and recovery. The last stage, lasting from 1996 to 2009, was characterized by dynamic growth of production and sales. The new family of regional jets (ERJ-145 and Embraer 170/190) turned out to be a great selling success which has enabled the company to maintain its position as a global leader in regional jets, which vies with the Canadian Bombardier for the third place in the world ranking of aircraft manufacturers.